Valoração de intangíveis no contexto de negociação e transferência de tecnologias desenvolvidas em universidades públicas brasileiras - Elimar Pires Vasconcellos (2015)
Universities and research centers have a key role in the innovation process, ranging from training of skilled manpower, publication of scientific and technical information, development of tools and prototypes, to more direct roles of fostering the innovation process as joint research and development (R&D) with companies, technology transfer and creation of spin offs. In the Brazilian scenario, with increasing scientific production, the technology transfer process is still incipient. The Innovation Law, key milestone regarding policies to foster technological innovation and interaction with research institutions, formalizes the role of universities in participating in the innovation process and provides guidance and sets important structures so that the relationship between universities and companies may be established. The technology transfer offices (NITs), created by that law, have the role of protecting the intellectual property of technologies developed in Brazilian public universities, as well as to manage their transfer to the market. The valuation of these technologies, especially to create bases for the negotiation process with companies and other institutions, stands out among the challenges faced by NITs. It was studied the applicability of methods of valuation based on costs, multiples, discounted cash flow and real options in the process of technology transfer, as well as the 25% rule on setting royalties. Based on this analysis, as well as on industry analysis from other studies, it was developed a tool to support the decision making process for innovation agents.